A Comparison of Energy Usage in the Home Canning of Tomato Juice - Che Man, Yaakob; Collins, Jimmie L. (1982)
A study on the heat processing of tomato juice was conducted using a low water level (LWL) hot water bath in comparison to the conventional recommended high water level (HWL) bath procedure. The L WL bath contained one-fifth the amount of water recommended for the HWL bath. The results indicated that the temperatures of the juice during processing were similar in both procedures. However, use of the HWL bath required 59 minutes and 1838 watt-hours of electricity to heat the bath and process hot packed (920 C) juice for 15 minutes. In contrast, only 34 minutes and 1065 watt-hours ofelectricity were required when the L WL bath was used.